Ukuran Tubuh Entok di Tiga Kabupaten Provinsi Jawa Tengah - Fatmarischa, N.; Sutopo, Sutopo; Johari, S. (Universitas Sebelas Maret (UNS), 2013)
The study was conducted to identify the body measurements of Muscovy duck among threeregency (Pekalongan, Magelang dan Demak) in Central Java. Material of the experiment was 210 muscovy ducks at 7 months of age (70 birds/regency, 35 males and 35 females). Parameters observed were body weight, bill length, bill width, head length, head circumference, high head, neck length, neck circumference, wing length, body length, breast circumference, body height, breast length, femur length, tibia length, tibia circumference, maxilla length, and length of third toe. Data of body measurement were analyzed through univariate and multivariate using SAS.Whereas the Mahalanobis distance were analyzed using MEGA 5 (UPGMA) to construct the phylogeny tree. Result showed that there were some differences (P<0,05) between male and female of muscovy duck in each regency at all variables. Wing length and breast circumference were the distinguishing variable between regencys. Muscovy duck from Magelang had a closer genetic distance to Pekalongan than Demak.Keywords: body measurement, muscovy duck